STUDI TENTANG PENGELOLAAN KEUANGAN DAERAH PERSPEKTIF PERMENDAGRI NO. 13 TAHUN 2006 PADA PEMERINTAH PROVINSI KALIMANTAN TIMUR - Mukaddas, Al (Journal of Innovation in Business and Economics, 2013)
Abstract This study was conducted to determine the authority on financial management of East Kalimantan, analyze the financial management, and identify the regional authority perspective of east Kalimantan as stated in the Regulation of Minister of Home Affairs No. 13 in 2006 as the embodiment of good governance. The data used in this study was in the form of qualitative data which was obtained from the government of East Kalimantan and processed by applying qualitative descriptive analysis method and investigated using explorative approach. The results showed that the process of regional budget preparation of East Kalimantan has fully reflected the aspirations of the local community, the implementation of financial management has been organized effectively and efficiently in accordance with the idea of the Supreme Audit Institution (BPK)presented in the financial statements of East Kalimantan in 2012 which obtained the qualification criteria that meet the expectations. In addition, the province inspectorate board has executed their duty to control the financial management satisfactorily where the testing accountability was completely supported by sufficient evidence and the results of the annual review of financial statements performed by Local Government Agencies (SKPD)